Religion and violence in a globalised world - Wolfgang Huber (Verbum et Ecclesia, 2011)
Violent religious extremism is seen as one of the mega-problems of the 21st century. This article based on a key lecture at the conference on Violence in a democratic South Africa at the University of Pretoria and the David de Villiers memorial lecture at the University of Stellenbosch, both held during August 2010 critically discussed the interaction between religion and violence in our present-day, globalised world. Three different propositions on the relationship between religion and violence were scrutinised. In countering the proposition that religion, or more specifically monotheism, necessarily leads to violence, it was argued that violence is not an inherent, but rather an acquired or even an ascribed quality of religion. The second proposition that religion leads to non-violence was affirmed to the extent that religions do provide a strong impulse to overcome violence. However, they also tend to accept violence as an inevitable part of reality and even justify the use of violence on religious grounds. The third proposition was regarded as the most convincing, for it argues that the link between religion and violence is contingent. Some situations do seem to make the use of violence inevitable; however, religions should refrain from justifying the use of violence and maintain a preferential option for nonviolence.